Building Islamic Boarding School Economic Independence through Cooperatives: The Role of Edupreneurship - Jannah, Lu'luatul; Ainol Yaqin (Journal of Educational Management Research, 2025)
The purpose of this study is to analyze the role of cooperatives in promoting the economic independence of Islamic boarding schools through the concept of edupreneurship. This study aims to explore how cooperatives can serve as a means to enhance the financial viability of Islamic boarding schools, as well as a platform for students to develop entrepreneurial skills. The research method employed is a qualitative approach, utilizing case studies of several Islamic boarding schools with active cooperatives. Data collection was conducted through interviews, observations, and document reviews. The results of the survey indicate that Islamic boarding school cooperatives play a crucial role in supporting economic independence by providing the financial services and resources necessary for Islamic boarding schools. Additionally, cooperatives offer students opportunities to learn about business management, financial planning, and entrepreneurship. The implications of this study suggest that strengthening Islamic boarding school cooperatives, combined with the concept of edupreneurship, can create a sustainable economic empowerment model and enhance the quality of education in Islamic boarding schools by developing practical skills relevant to market needs.